2015
DOI: 10.1103/physreva.91.033833
|View full text |Cite
|
Sign up to set email alerts
|

Twisted anisotropic fibers for robust orbital-angular-momentum-based information transmission

Abstract: We study the light propagation in the twisted anisotropic optical fibers endowed with torsional mechanical stress by obtaining the analytical solution o f the vector wave equation. We show that at certain interplay between fiber parameters optical vortex beams o f topological charge l = 0 ,± 1 ,± 2 ,... become the modes o f the fibers in question. To explain the splitting of the optical vortex propagation constants we introduce the notions of orbital birefringence and optical Zeeman effect. Moreover, we unveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
1
28
0
2
Order By: Relevance
“…The OAM birefringence displayed by twisted multicore PCFs is of interest in OAM-based optical communications [35,36] and may also be useful for flexible transmission of OAM in laser tweezer experiments for manipulation, for example, of cells.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OAM birefringence displayed by twisted multicore PCFs is of interest in OAM-based optical communications [35,36] and may also be useful for flexible transmission of OAM in laser tweezer experiments for manipulation, for example, of cells.…”
Section: Applicationsmentioning
confidence: 99%
“…Similar experiments carried out at multiple wavelengths and for fibre lengths up to 50 m confirmed that the twisted PCFs preserve the magnitude and sign of the OAM. The OAM birefringence displayed by twisted multicore PCFs is of interest in OAM-based optical communications [35,36] and may also be useful for flexible transmission of OAM in laser tweezer experiments for manipulation, for example, of cells.…”
Section: (C) Orbital Angular Momentum-based Telecommunications Optical Tweezersmentioning
confidence: 99%
“…Twisted multicore PCFs have been shown to support helical Bloch waves and to exhibit orbital angular momentum (OAM) birefringence ( 9 ). There have also been many theoretical studies, for example, of spin-orbit coupling ( 10 , 11 ) and Bloch dynamics in helical coupled waveguide arrays ( 12 ). …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the impact of twisting on the properties and stability of self-sustained vortex states in the nonlinear regime has not been addressed, neither in ring-like arrays nor in rotating lattices, such as those described in [66][67][68][69][70][71]. Such rotating structures can be created using interfering nondiffracting beams [72,73] propagating in photosensitive materials [74][75][76], or as photonic crystal fibers twisted during drawing process [77][78][79]. The non-degeneracy of linear vortex modes with opposite charges occurs in linear twisted photonic crystal fibers [80] and is suggested by the excitations in optically-induced structures [76], but it has not been addressed directly in the nonlinear regime.…”
mentioning
confidence: 99%